PENGARUH PEMBIAYAAN MURABAHAH, MUDHARABAH DAN IJARAH TERHADAP TINGKAT LABA BERSIH PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2015-2019 - Ajeng Puspita Dewi; Wirman (Universitas Islam Negeri Mataram, 2023)
The purpose of this study was to determine the effect of Murabahah, Mudharabah, and Ijarah Financing on the Net Profit Rates of Islamic banks in Indonesia. This research uses the positivism paradigm with a quantitative approach. The population in this study were all Sharia Commercial Banks registered at Bank Indonesia while the sampling technique used purposive sampling techniques and obtained 3 Sharia Commercial Banks. The data analysis method used in this study is multiple linear regression analysis. The results of this study are murabaha financing has a significant effect on net income and mudharabah financing does not significantly influence net income, while Ijarah financing does not significantly influence net income.